Functional monoesters of jojoba oil can be produced by enzymatic interesterification : reaction analysis and structural characterization - Lei, Qiong (2015)
Long-chain monounsaturated fatty acid ethyl esters (LMFAEE) and fatty alcohol acetates (LMFAA) are important functional compounds in industry, and new sources are needed. In this study, jojoba oil was interesterified with ethyl acetate (EA) for the combined production of LMFAEE and LMFAA. Lipozyme RM IM and Novozym 435 were employed as the biocatalyst and their efficiencies were compared. Aliquot removal and subsequent 1H NMR analysis were used to monitor reaction progress and determine the interesterification yield (IY, %). Optimization of this reaction was conducted for both lipases with respect to four experimental parameters: temperature, EA content, immobilized lipase load, and reaction time. The highest IY in the presence of Novozym 435 was 97%, which was achieved after 9 hours of reaction at 37°C with 75 wt% EA and 5.00 wt% lipase load at 300 rpm, whereas the IY was 76% in the case of Lipozyme RM IM. The interesterified product was purified by preparative TLC and characterized by 1H NMR, FT-IR and GC-MS, indicating the main components are ethyl cis-11-eicosenoate (44%), cis-11-eicosenyl acetate (25%) and cis-13-docosenyl acetate (22%). Novozym 435 exhibited excellent operational stability over 17 interesterification cycles with ca. 12% IY decrease.